Increasing hernia size requires higher GRIP values for a biomechanically stable ventral hernia repair - Kallinowski, Friedrich; Gutjahr, D.; Vollmer, Matthias; Harder, Felix; Nessel, R. (Annals of medicine and surgery, 2019)
Background: Increasing hernia sizes lead to higher recurrence rates after ventral hernia repair. A better grip might reduce the failure rates. Material and methods: A biomechanical model delivering dynamic intermittent strain (DIS)was used to assess grip values at various hernia orifices. The model consists of a water-filled aluminium cylinder covered with tissues derived from pig bellies which are punched with a central defect varying in diameter. DIS was applied mimicking coughs lasting for up to 2 s with peak pressures between 180 and 220 mmHg and a plateau phase of 0.1 s. Ventral hernia repair was simulated with hernia meshes in the sublay position secured by tacks, glue or sutures as needed to achieve certain grip values. Grip was calculated taking into account the mesh: defect area ratio and the fixation strength. Data were assessed using non-parametric statistics. Results: Using a mesh classified as highly stable upon DIS testing (DIS class A)a reduced overlap without fixation led to early slippage (p < 0.001). With the application of 16 fixation points, transmural sutures were better than tacks with Securestrap ® being better than Absorbatack ® (p < 0.001). Plotting the likelihood of a durable repair as a function of the calculated grip higher grip values were needed with increasing hernia diameter to achieve biomechanical stability. This is important for clinical work since the calculated grip values both from a registry and from published data tend to drop as hernia sizes increase indicating biomechanical instability. Conclusion: The experimental work reported here demonstrates for the first time that higher grip values should be reached when repairing larger ventral hernias.